0465 Structural And Functional Properties Of Thoracic Ascending Aorta In Obstructive Sleep Apnea (the Multi-ethnic Study Of Atherosclerosis [mesa] Study). (27th April 2018) - Kwon, Y; Logan, J; Redline, S; Duprez, D; Jacobs, D R; Ouyang, P; Hundley, W G; Lima, J; Bluemke, D A; Lutsey, P L
Abstract: Introduction: Structural and functional properties of the proximal aorta have important implications in clinical and subclinical cardiovascular disease (CVD). Long term exposure to obstructive sleep apnea (OSA) may have an adverse impact on aortic properties through exaggerated intrathoracic pressure change, sympathetic activation and intermittent hypoxemia. We sought to examine whether OSA is associated with proximal aortic size and aortic stiffness in a community-based cohort. Methods: MESA study participants without prevalent CVD who underwent polysomnography as part of an ancillary study were included. Ascending aortic diameter at pulmonary artery bifurcation level (AscAoD [cm]), aortic pulse wave velocity (AoPWV [m/sec]) and aortic distensibility (AoD [%/mmHg]) were measured by cardiac magnetic resonance imaging. Multiple linear regression was used to compare aortic properties across three apnea hypopnea index (AHI)-based severity groups, adjusting for age, gender, race, body surface area, systolic blood pressure, diabetes, smoking and cholesterol levels. Results: The 708 participants were 55.9% female and on average 68 years old [54–93 years]. There was a significant trend (p=0.001) of greater mean [SD] AscAoD across the three OSA groups: normal (AHI<5/hr; n=87) = 3.19 [0.35]; mild (AHI 5–15; n=215) = 3.31 [0.34]; moderate to severe (AHI ≥15; n=406) = 3.44 [0.36]). In multivariable analysis, participants with moderate to severe OSA, but not mild OSA, had significantly greater adjusted mean [95% CI] AscAoD compared with the normal group: adjusted mean difference [95% CI] = 0.12 [0.05, 0.20], p= 0.002 (moderate to severe vs. normal group), 0.07 [-0.001, 0.15], p=0.08 (mild vs. normal group). In contrast, no significant differences were found with AoPWV or AoD and OSA group: AoPWV: 0.48 [-0.46, 1.41], p= 0.32 (moderate to severe vs. normal group), -0.06 [-1.01, 0.9], p=0.91 (mild vs. normal group); AoD: 0.17 [-0.11, 0.44], p= 0.23 (moderate to severe vs. normal group), -0.04 [-0.32, 0.24], p=0.78 (mild vs. normal group). Conclusion: In a racially/ethnically diverse community cohort, presence of moderate to severe OSA (vs. absence of OSA) was associated with slightly greater ascending aortic diameter. Support (If Any): NIH.